2005
DOI: 10.1021/es0507517
|View full text |Cite
|
Sign up to set email alerts
|

Geographical, Spatial, and Temporal Distributions of Multiple Indoor Air Pollutants in Four Chinese Provinces

Abstract: Exposure to indoor air pollution from household energy use depends on fuel, stove, housing characteristics, and stove use behavior. We monitored three important indoor air pollutants-respirable particles (RPM), carbon monoxide (CO), and sulfur dioxide (SO2)-for a total of 457 household-days in four poor provinces in China (Gansu, 129 household-days; Guizhou, 127 household-days; Inner Mongolia, 65 household-days; and Shaanxi, 136 household-days), in two time intervals during the heating season to investigate sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 20 publications
7
59
4
1
Order By: Relevance
“…Differences in indoor and outdoor air quality among various rooms in rural Chinese households have been reported, with the most severe pollution often occurring in kitchens (Jiang and Bell 2008). Another research monitored three important indoor air pollutants: respirable particles, CO and SO 2 , in four poor provinces in China and came to the conclusion of distributions of multiple indoor air pollutants (Jin et al 2005). Similar researches were also done in other countries.…”
Section: Introductionmentioning
confidence: 80%
“…Differences in indoor and outdoor air quality among various rooms in rural Chinese households have been reported, with the most severe pollution often occurring in kitchens (Jiang and Bell 2008). Another research monitored three important indoor air pollutants: respirable particles, CO and SO 2 , in four poor provinces in China and came to the conclusion of distributions of multiple indoor air pollutants (Jin et al 2005). Similar researches were also done in other countries.…”
Section: Introductionmentioning
confidence: 80%
“…"Daily average" and "1-h peak" concentrations of CO were 5.7 and 14.0 ppm for wood and 6.0 and 10.3 ppm for coal, respectively. Jin et al (2005) measured that daily CO concentration from coal burning in Guizhou ranged from 1.0 to 2.1 ppm in both cooking room and bedroom. further presented that daily CO concentrations from coal burning in Guizhou were 3.2 ppm in the cooking room and 4.1 ppm in the bedroom, respectively.…”
Section: Indoor Co and Particulate Matter (Pm) Concentrationsmentioning
confidence: 99%
“…Indoor emissions from household fuel burning were carried out in some rural areas in China (Sinton et al, 2004;He et al, 2005;Jin et al, 2005;Fischer et al, 2007). However, these studies scarcely have reported time-resolved concentrations of indoor air pollutants, which may be valuable in improving exposure assessment (Fischer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…물 등 주요 오염원이기도 하다 (Shuxiao et al, 2009;Yan et al, 2006;Guo et al, 2006Guo et al, , 2004Bates, 2005;Jin et al, 2005;Tonooka et al, 2001). N a p h t h a l e n e A c e n a p h t h y l e n e A c e n a p h t h e n e F l u o r e n e P h e n a n t h r e n e A n t h r a c e n e F l u o r a n t h e n e P y r e n e B e n z ( a ) a n t h r a c e n e C h r y s e n e B e n z o ( b ) fl u o r a n t h e n e B e n z o ( k ) fl u o r a n t h e n e B e n z o ( a ) p y r e n e I n d e n o ( 1 , 2 , 3 -c d ) p y r e n e D i b e n z ( a , h ) a n t h r a c e n e B e n z o ( g , h , i ) p e r y l e n e …”
Section: 서 론unclassified